2017
DOI: 10.28998/rca.v14i1.2298
|View full text |Cite
|
Sign up to set email alerts
|

CONTROLE EM PÓS-EMERGÊNCIA DE Conyza canadensis e Conyza bonariensis COM EXTRATOS DE Canavalia ensiformis

Abstract: <p>Avaliou-se o efeito alelopático dos extratos aquoso e etanólico de folhas de <em>Canavalia ensiformis </em>no controle em pós-emergência das espécies <em>Conyza canadensis </em>e <em>Conyza bonariensis</em>. Para isso, foram preparados extratos aquoso e etanólico nas concentrações: 10, 25, 50, 100 e 150 g.L<sup>-1</sup>. Para a avaliação do efeito alelopático, os extratos foram aplicados no estádio de dois e quatro pares de folhas e a plântulas avaliadas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Analyzing the data presented in Table 9, it can be concluded that C. spectabilis synthesizes allelopathic substances with a high suppression capacity of Conyza bonariensis, preventing its germination and development, a very positive result, considering that this herb is difficult to control, containing biotypes resistant to glyphosate, according to Mendonça et al (2016). However, it was not efficient in controlling the other herbs present.…”
Section: Methodsmentioning
confidence: 99%
“…Analyzing the data presented in Table 9, it can be concluded that C. spectabilis synthesizes allelopathic substances with a high suppression capacity of Conyza bonariensis, preventing its germination and development, a very positive result, considering that this herb is difficult to control, containing biotypes resistant to glyphosate, according to Mendonça et al (2016). However, it was not efficient in controlling the other herbs present.…”
Section: Methodsmentioning
confidence: 99%